PENDAMPINGAN PEMBUATAN LEMBAR KEGIATAN SISWA DARING UNTUK IMPLEMENTASI KEBIJAKAN BELAJAR DARI RUMAH BAGI GURU DI KOTA BENGKULU - Endang Widi Winarni; Irwan Koto (UNIVERSITAS BENGKULU, 2021)
One of the impacts of COVID-19 pandemic is forcing teachers and school residents to adjust teaching and learning activities at home. This mentoring activity aims to improve the knowledge and skills of SD N 69 Bengkulu City teachers to prepare worksheets that are easy for parents to understand while implementing BDR. This service activity partners are grade 1 to grade 6 teachers of SDN 69 Bengkulu City, class, religion, and health education teachers, totaling 26 teachers. This activity was carried out from August to November 2020 through observational and modeling with four phases, namely: the attention phase, the retention phase, the reproduction phase, and the motivation phase. The instrument used was a questionnaire to measure teacher knowledge about online worksheets and a rubric for assessing teacher skills in compiling online worksheets. Results and conclusions, teacher assistance activities to prepare online worksheets can: (1) Increase teachers' knowledge about online worksheets, especially those related to online worksheets' goals. (2) Improve teacher skills in compiling online worksheets, especially the fourth aspect, namely teachers' skills to collect assessment rubrics per basic subject competence in online worksheets.